Evolution and oncological outcomes of a contemporary radical prostatectomy practice in a UK regional tertiary referral centre. (24th May 2016) - Gnanapragasam, Vincent J.; Thurtle, David; Srinivasan, Anandagopal; Volanis, Dimitrios; George, Anne; Lophatananon, Artitaya; Stearn, Sara; Warren, Anne Y.; Lamb, Alastair D.; Shaw, Greg; Sharma, Naomi; Thomas, Ben C.; et al.
Abstract : Objective: To investigate the clinical and pathological trends, over a 10‐year period, in robot‐assisted laparoscopic prostatectomy (RALP) in a UK regional tertiary referral centre. Patients and Methods: In all, 1 500 consecutive patients underwent RALP between October 2005 and January 2015. Prospective data were collected on clinicopathological details at presentation as well as surgical outcomes and compared over time. Results: The median (range) age of patients throughout the period was 62 (35–78) years. The proportion of preoperative high‐grade cases (Gleason score 8–10) rose from 4.6% in 2005–2008 to 18.2% in 2013–2015 ( P < 0.001). In the same periods the proportion of clinical stage T3 cases operated on rose from 2.4% to 11.4% ( P < 0.001). The median prostate‐specific antigen (PSA) level at diagnosis did not alter significantly. Overall, 11.6% of men in 2005–2008 were classified preoperatively as high‐risk by National Institute for Health and Care Excellence criteria, compared with 33.6% in 2013–2015 ( P < 0.001). The corresponding proportions for low‐risk cases were 48.6% and 17.3%, respectively. Final surgical pathology showed an increase in tumour stage, Gleason grade, and nodal status over time. The proportion of pT3 cases rose from 43.2% in 2005–2008 to 55.5% in 2013–2015 ( P < 0.001), Gleason score 9–10 tumours increased from 1.8% to 9.1% ( P < 0.001) and positive nodal status increased from 1.6% to 12.9% ( P < 0.001) between the same periods. Despite this, positive surgical margin rates showed a downward trend in all pT groups across the different eras ( P = 0.72). Conclusion: This study suggests that the patient profile for RALP in our unit is changing, with increasing proportions of higher stage and more advanced disease being referred and operated on. However, surgical margin outcomes have remained good.